Signcryption with Matrix Modification of RSA Digital Signature Scheme and Cayley-Purser Algorithm - Ginting, Cindy Laurent; Budiman, Mohammad Andri; Nasution, Sawaluddin (Talenta Publisher, 2024)
The sender must ensure the security of messages and authenticated messages in messaging communications. Additionally, the sender must guarantee the message's integrity and cannot deny its authenticity or involvement with the message. This aspect is more robust because the recipient can verify, ensuring that the message originates from an authorized sender. In addition to this crucial aspect, the Signcryption method employing the Matrix Modification of RSA Digital Signature Scheme and the Cayley-Purser Algorithm can accomplish both of the objectives of this study. Encrypt-then-sign is the Signcryption method used, and the MD5 hash function performs one-way hashing during the signing procedure to enhance message security. This study tested the message plaintext in the form of a collection of strings consisting of uppercase (capital), lowercase (small), numbers (numeric), and other punctuation characters with varying numbers of characters in each string, as well as the value of modulus n from 10 digits up to its maximum length, which is unconstrained. The test results indicate that the time required for encryption and decryption is proportional to the number of plaintext characters used.